Apocynaceae s. str. do Parque Nacional da Serra da Canastra (MG) e anatomia floral de Condylocarpon isthmicum (Vell.) A. DC. (Rauvolfioideae) - Morokawa, Rosemeri, 1980- (2009)
Orientadores: Luiza Sumiko Kinoshita, Andre Olmos Simões